2017
DOI: 10.1177/1526924817746684
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neighbor Effect and Urbanization Toward Organ Donation in Thailand

Abstract: This article documents the "neighbor effect" on the organ donation decision via living area type, offering an alternative exposition in raising the organ donation rate. In shifting the society norm toward organ donation consent, policy-makers should acknowledge the benefit of urbanization on organ donation decision derived from resourceful urban areas. Moreover, raising education levels does improve not only citizens' well-being but also their tendency to exhibit an altruistic act toward others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The rate of organ donation is quite low in Thailand. It depends on the patients, religious beliefs of the relatives, the neighbor effect, 38 preparedness of the transplant center, and national policy.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of organ donation is quite low in Thailand. It depends on the patients, religious beliefs of the relatives, the neighbor effect, 38 preparedness of the transplant center, and national policy.…”
Section: Discussionmentioning
confidence: 99%
“…33 Another study conducted in Thailand showed that even higher SES of neighbors has positive impact on WTD. 34 Although a great number of authors have reported the significant influence of the socioeconomic variables of education and income on WTD organs, there is lack of consensus on whether this influence is positive or negative. 35,36 On the one hand, a study on Malaysia reported a significant influence of SES on WTD, 27 which is corroborated by studies conducted in Europe and Canada.…”
Section: Factors Influencing Wtdmentioning
confidence: 99%